2009
DOI: 10.1002/gcc.20720
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary gastrointestinal stromal tumors sharing the KIT Exon 17 germline mutation p.Asp820Tyr develop through different cytogenetic progression pathways

Abstract: Hereditary gastrointestinal stromal tumor (GIST) syndrome is a rare autosomal dominant genetic disorder originated by germline mutations in the KIT or PDGFRA genes. We report the third family with hereditary predisposition to GIST due to the KIT Exon 17 germline mutation p.Asp820Tyr and characterize the cytogenetic progression pathways followed by different GIST sharing the same primary genetic event, using a combination of chromosome banding, comparative genomic hybridization (CGH), and fluorescence in situ h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 45 publications
2
17
0
Order By: Relevance
“…Indeed, one patient with an intestinal lesion with less than 2 cm and low mitotic rate (patient 20, categorized in the low-risk group) developed metastases and died from the disease 11 months after diagnosis. More recently, anatomic location was also considered of relevance and included in the determination of the risk of recurrence and progression [21,24]. Our findings strongly support this prediction model, as a significant proportion of small intestine or colon GIST developed metastasis, whereas most tumors located in the stomach showed no progression events.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Indeed, one patient with an intestinal lesion with less than 2 cm and low mitotic rate (patient 20, categorized in the low-risk group) developed metastases and died from the disease 11 months after diagnosis. More recently, anatomic location was also considered of relevance and included in the determination of the risk of recurrence and progression [21,24]. Our findings strongly support this prediction model, as a significant proportion of small intestine or colon GIST developed metastasis, whereas most tumors located in the stomach showed no progression events.…”
Section: Discussionsupporting
confidence: 82%
“…Mutations were detected in 61 tumors (76.25%, Figure 1), namely in exon 11 (n = 52), exon 9 (n = 7) and exon 17 (n = 2). The two patients with KIT exon 17 mutation were subsequently found to be relatives and the mutation shown to be present in the germline [21]. No primary mutations were found in exon 13.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They occurred at earlier ages than corresponding sporadic GISTs, commonly in young adults, and median age at diagnosis is approximately 40–50 years. Some authors have suggested a possible genetic anticipation because of decreasing age at diagnosis across generations 141,144,150. However, it was not reported previously, and earlier ages at diagnosis might be only due to greater interest for GISTs and/or screening of relatives.…”
Section: Genetic Predispositionmentioning
confidence: 91%
“…Today, 16 different germline mutations involving exons 8, 11, 13, or 17 of KIT or exons 12 or 14 of PDGFRA have been reported to our knowledge (Table 3). 131150 In all publications, the pattern of inheritance is autosomal dominant with a penetrance of almost 100%. GISTs are multiple in most cases and frequently multifocal.…”
Section: Genetic Predispositionmentioning
confidence: 99%